Usability Testing on The Mobile Gras (Green Trash System) Application Using The Usability Scale System Method - I Gusti Made Ngurah Desnanjaya; I Kadek Budi Sandika; Ida Bagus Gede Sarasvananda; Putu Wirayudi Aditama; I Komang Arya Ganda Wiguna (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2023)
This study focuses on the GRAS (Green Trash System) mobile application, developed under the KEDAIREKA program to enhance waste management efficiency. The application is an integral part of the GRAS smart waste system, designed to facilitate real-time monitoring and reporting of waste capacity issues. The primary objective is to streamline waste sorting processes and educate users, particularly students, about sustainable waste management practices. The system features innovative sensor technology that provides audio feedback for correctly sorted waste, thus reinforcing correct behaviors. To assess the application's effectiveness, we conducted a usability test using the System Usability Scale (SUS) method. Data were collected through questionnaires to evaluate the application's ease of use, efficiency, and user satisfaction. The results indicated a high level of usability, with most users experiencing seamless interaction with the application, affirming its potential as a tool for effective waste management education and practice.